2004
DOI: 10.1016/j.ijheatmasstransfer.2004.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh Bénard convective instability of a fluid under high-frequency vibration

Abstract: The generation of two-dimensional thermal convection induced simultaneously by gravity and high-frequency vibration in a bounded rectangular enclosure or in a layer is investigated theoretically and numerically. The horizontal walls of the container are maintained at constant temperatures while the vertical boundaries are thermally insulated, impermeable and adiabatic. General equations for the description of the time-averaged convective flow and, within this framework, the generalized Boussinesq approximation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…On the other hand, under normal gravity conditions, Gershuni et al (24) theoretically analyzed the linear stability of double diffusive convection in the presence of high-frequency vibration and determined the conditions of quasi-equilibrium. It was further found that vibration can generate or delay convective instabilities depending on the mutual orientation of the vibration axis and gravity (25,26). Specifically, vertical vibration that is parallel to the gravity has been used to stabilize the unstable thermal gradients (27), even in the turbulent regime (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, under normal gravity conditions, Gershuni et al (24) theoretically analyzed the linear stability of double diffusive convection in the presence of high-frequency vibration and determined the conditions of quasi-equilibrium. It was further found that vibration can generate or delay convective instabilities depending on the mutual orientation of the vibration axis and gravity (25,26). Specifically, vertical vibration that is parallel to the gravity has been used to stabilize the unstable thermal gradients (27), even in the turbulent regime (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental treatise [1] comprises a systematic study of convective flows induced by high and finite frequency vibrations in closed and infinite cavities. Thermovibrational convection in square, rectangular, and cubic cavities was widely investigated providing a variety of mean flow structures and bifurcation scenarios [5][6][7][8]. Influence of vibration on double diffusive convection with the Soret effect was analyzed in [9].…”
mentioning
confidence: 99%
“…Secondary forcing can also be used delay or manipulate the Rayleigh-Bénard instability. As with the Rayleigh-Taylor instability, high frequency vertical vibrations (in this case, parallel to the temperature gradient) can suppress convection [30,61,160] as can modulation of the applied temperatures [31] or the addition of an oscillatory shear flow [76]. Closed-loop (feedback) control strategies have been investigated, with many based on the application of inhomogeneous perturbations to the heat flux at the lower boundary [67,116].…”
Section: Strategies For Controlmentioning
confidence: 99%